Implementasi Manajemen Talenta dan Pengaruhnya terhadap Retensi Karyawan di Perusahaan Teknologi - Galang Semesta Fauzi; Edi Suryadi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study addresses the critical challenge of employee retention in technology companies, where rapid innovation and intense competition create high turnover risks. The research aims to analyze how talent management practices contribute to strengthening retention strategies and to propose a comprehensive conceptual framework for digital-era organizations. Using a qualitative documentary approach, the study examines secondary data from 2020-2024, including corporate reports, academic publications, and industry surveys. The findings reveal that effective talent management requires an integrated perspective that combines leadership development, continuous performance evaluation, personalized training programs, and the adoption of advanced technologies such as predictive analytics and artificial intelligence. Key factors influencing retention include competitive and holistic compensation packages, transparent career progression, inclusive workplace culture, flexible working arrangements, and comprehensive well-being initiatives. This research contributes to human resource management literature by highlighting the multidimensional relationship between talent management and employee retention, while offering practical recommendations for designing adaptive and sustainable retention strategies in the technology sector.